Teachers' perceptions on transformational leadership based on demographic differences - Talebloo, Baharak; Basri, Ramli; Asimiran, Soaib; Hassan, Aminuddin (IDOSI Publications, 2015)
Transformational leadership emphasizes emotions and values sharing and aims at fundamental reform of individuals and the whole organization capacity. It has contributed to development in terms of motivation and commitment in problem solving as well as implementation of reform initiative. The purpose of this study was to determine the level of transformational leadership in primary schools in Malaysia based on demographic differences. 144 primary school teachers from 24 schools in six district of Selangor were selected based on stratified random sampling. Data were collected based on survey method and were analysed using descriptive and independent t-sample test and one way-ANOVA. According to the findings the level of transformational leadership was high based on teachers’ perceptions. Furthermore, result of analysis indicated that there among transformational leadership dimensions there was significant difference between national, chines and Tamil teachers’ perception in individualized support and collaborative in decision making. The findings based on differences in transformation leadership by location showed that teacher perceptions in urban area higher in modelling behaviour and straight school culture than the rural teacher’s perceptions. The findings of this study have implications for how close or far the schools move towards 2010 Malaysia vision and which transformational leadership factors need to be focused on more.